Management non-profit organizations: an assessment of performance through the balanced scorecard - Júnior, Jorge Assef Lutif; Queiroz, Jamerson Viegas; Hékis, Hélio Roberto; Queiro, Fernanda Cristina Barbosa Pereira; Lima, Nilton Cesar; Furukava, Marciano (Brazilian Journal of Operations & Production Management, 2014)
The methodology Balanced Scorecard (BSC) focuses on the major critical issues of modern organizations, whether with or without profit. The measurement of the effective performance of the latter is by evaluating the successful implementation of organizational strategy. The main results of the proposed approach refers to evaluation of overall scores for each dimension of the BSC methodology, financial, customer, internal processes, learning and growth. These results are able to help the organization evaluate and revise their strategy and, in general, to adopt management methods more accurately. The findings highlight on balancing and alignment of strategic objectives, low causality map, strategic communication insufficient and fragmented. The performance indicators portray more meritocracy operational procedures of social projects in the context of the Strategic Map determined in a short-term over the long term. However, there is evidence of improved performance management and strategic taken as a basis of planning as both the strategic map structured. Therefore, the nonprofits need to adopt a form of management that enables planning, setting objectives and targets that provide the continuity of its activities, and generating instruments that can measure the financial performance and non-financial, in order to develop strategic actions for growth and sustainability.